Mental Health And Moral Education In Robert Frager's Transformative Psychology - Muhtar Gojali (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This paper examines mental health and moral education from the perspective of psychology by Robert Frager. The object of this research is literature. So that this research can be categorized as library research [1], in this study, the authors used a qualitative approach. The primary data in this study is the work of Robert Frager, “Heart, Self, & Soul: The Sufi Psychology of Growth, Balance, and Harmony, published by Theological Publishing House, Wheaton, 1999. This study found that according to Robert Frager, mental health can be achieved by how to practice the five spiritual paths, namely, way of heart, mind, group, service, and remembrance. In addition, the author also finds that according to Robert Frager, moral education can be carried out by simultaneously integrating the three spiritual organs of man, namely, heart, self, and soul.